Digital payments enhance both formal and informal credit access for rural households: evidence from China - Chen, Baozhen; Xiao, Jialin (Frontiers in Sustainable Food Systems, 2025)
While digital finance is recognized for enhancing financial inclusion, its micro-level mechanisms—particularly through digital payments—remain underexplored. This study demonstrates how adopting digital payments significantly enhances Chinese farmers’ ability to obtain credit from both sources. Analyzing data from 7,522 households across diverse regions (2017–2019, 2021–2023) using robust methods to address endogeneity and selection bias, we find that digital payment adoption significantly increases farmers’ credit access overall. The findings indicate that digital payments alleviate conditional and price exclusion in formal credit markets, improve farmers’ credit knowledge, and reduce the psychological barriers of credit-constrained borrowers. Furthermore, digital payment adoption enhances informal credit capacity, providing farmers with more funding options. The digital payments enhanced farmers’ satisfaction with accessing credit, exerting a positive influence on both credit intended for agricultural production and credit intended for non-agricultural purposes. The results suggest that digital payment adoption not only enhances formal credit access but also strengthens informal credit networks, offering farmers greater flexibility in meeting their financial needs. Policymakers should prioritize the development of digital financial infrastructure and promote financial literacy to maximize the benefits of digital finance for rural households.